The influence of climate on varietal similarities across countries - Germán Puga; Kym Anderson (Agricultural & Environmental Letters)
Abstract In recent decades, vignerons have focused more on the world's mainstream varieties than on differentiating their varietal mix. This has led countries to become more similar to each other in their mix of winegrape varieties and more varietally concentrated. What are the drivers of those changes? In this study, we focus on one of those drivers, that is, climate similarities. We estimate statistical models to quantify the potential influence of 16 climate variables on varietal similarities across countries, as well as on how their varietal mixes have become more or less similar since 2000. The results indicate not only that countries with more similar climates have more similar varietal mixes but also that in recent years countries with more similar climates have become even more similar in their mixes. This, however, does not necessarily mean that vignerons have been planting the varieties that are better adapted to their climates. Core Ideas Wine‐producing countries have become more similar and concentrated in their mix of winegrape varieties. This similarity extends particularly among countries sharing similar climatic conditions. In recent years, countries with similar climates have continued to converge in their winegrape varietal mixes. Nevertheless, vignerons have not necessarily been planting varieties that are better suited to their climates.